PHENOMENOLOGICAL STUDY: THE EXPERIENCE OF BREASTFEEDING AMONG MOTHERS WHO ARE HIV-POSITIVE - Amalia Brilliandhini; Regina Vidya Trias Novita (Journal of Maternity Care and Reproductive Health, 2025)
The decision-making process regarding whether to breastfeed or not among mothers living with HIV is complex and influenced by multiple factors, including personal experiences, level of knowledge, cultural values and norms, and support from healthcare professionals. Mothers who choose to breastfeed often face ongoing anxiety related to potential risks and concerns about their infant’s health. Conversely, mothers who decide not to breastfeed may experience emotional conflicts, such as feelings of guilt and a diminished sense of confidence in fulfilling their maternal role.This study aims to explore the breastfeeding experiences of HIV-positive mothers with their infants using a qualitative phenomenological approach. Eight participants were selected through snowball and interviewed in depth using a semi-structured guide, and the data were analyzed thematically; the findings revealed five main themes, namely considerations in decision-making regarding infant feeding influenced by economic factors, recommendations from health professionals, and family support; mothers’ emotional reactions from the moment of HIV diagnosis characterized by shock, fear, confusion, mixed feelings during breastfeeding, and sadness or guilt for those who did not breastfeed; efforts to prevent HIV transmission by adhering to antiretroviral therapy (ART), maintaining hygiene of the breast and feeding equipment, practicing exclusive breastfeeding without mixing formula, and avoiding breastfeeding when nipples were injured; challenges and obstacles including social stigma, the financial burden of formula milk, lack of family support, and inconsistent medical information; and finally, support, information, and expectations, where mothers gained strength through regular consultations with healthcare providers, encouragement from husbands, and peer support from other HIV-positive mothers, while expressing hopes for more intensive assistance, continuous education, and more humanistic health services; this study concludes that infant feeding decisions among HIV-positive mothers are not merely medical issues but are shaped by the complex interaction of psychological, social, economic, and environmental support factors.